Detecting HIV-1 integration by repetitive-sampling Alu-gag PCR - Liszewski, Megan K. (2009)
In this review, we compare four assays that are currently used to measure HIV integration and discuss their strengths and weaknesses. We then outline advances that have been made toward development of a more robust, more sensitive, quantitative HIV integration assay suitable for clinical use. The assay that we have developed uses repetitive-sampling Alu-gag PCR. The detailed protocol describes our assay step-by-step, the creation of an integration standard cell line and accompanying standard curve, as well as the quantitation of integration and calculation of associated error estimates. Finally, we speculate on fundamental, unresolved issues in HIV latency that can be addressed by measuring HIV integration.